Technical evaluation of the desalination system of the Água Doce program in the municipality of Gravatá, PE - Almeida, Bruno Freire Maciel de; Fernandes, Amanda Cristiane Gonçalves (Brazilian Journal of Production Engineering, 2023)
This study aims to evaluate the effects of the desalination system belonging to the Fresh Water Program in a rural community in the municipality of Gravatá, semi-arid region of Pernambuco. For this, the methodology adopted was the use of cross-tabulation techniques of data in a GIS environment from the information collected in public platforms and technical reports, in which the spatial characterization of the region was carried out. In addition, a field visit was made, as well as contact with public agencies and the local community that benefited from this technology. Thus, it was evaluated that the system is extremely important for the community because there were benefits in the social and economic spheres. The amount of water refills through water tankers has decreased, there has been an improvement in the quality of the water through sensory reports from the families, and a decrease in water-related diseases. However, it was verified that the region lacks desalination technologies, moreover, an environmental impact related to the residual part of the desalination process was detected, the disposal of salt directly into the soil, causing its susceptibility through salinization.
Keywords: Social water technology; water Treatment; Groundwater.